All Days 1990
DOI: 10.2118/20606-ms
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Variability and Modeling with Fractals

Abstract: An important factor in the simulation of reservoir performance is the input reservoir parameters. Layers are often modeled with Constant parameters (porosity, permeability, etc.) or with only minor variations. The failure to incorporate appropriate heterogeneity into reservoir performance predictions can be a significant problem. This paper examines the variability in reservoir parameters as measured with wireline logs. Both vertical and horizontal well data are utilized for this purpose. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…These results are slightly lower than the 1.145 reported from a porosity log for a deep submarine fan sandstone (Hewett, 1986), and the average of 1.10 for density logs of a braided stream sandstone (Crane and Tubman, 1990). It is not clear whether this may be due to the different type of wireline logs used, or the different geological background.…”
Section: A Case Study Of Fractal Dimension Of Wireline Logsmentioning
confidence: 56%
See 1 more Smart Citation
“…These results are slightly lower than the 1.145 reported from a porosity log for a deep submarine fan sandstone (Hewett, 1986), and the average of 1.10 for density logs of a braided stream sandstone (Crane and Tubman, 1990). It is not clear whether this may be due to the different type of wireline logs used, or the different geological background.…”
Section: A Case Study Of Fractal Dimension Of Wireline Logsmentioning
confidence: 56%
“…Mathews et al (1989) used a fractal method for fluid-flow prediction in a channel-sands reservoir, and decided that the results were better than from traditional approaches. Crane and Tubman (1990) applied fractals to both vertical and horizontal well logs, in order to examine the spatial variability of reservoir porosity, and discovered similar fractal dimensions. They also used Fourier transform techniques to generate fractal reservoir realisations.…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that the logs analyzed by many authors in many different formations show similar to fGn; for example, Carne and Tubman analyzed three horizontal wells and four vertical wells in a carbonate formation. They found that all the logs behave as fGn (Crane and Tubman 1990). Moreover, Hardy found similar results by analyzing some wells in sandstone formations (Hardy 1993).…”
Section: Fractal Modelingmentioning
confidence: 75%
“…He found that black and white area distribution vertically and laterally has the characteristics of fGn. Crane and Tubman [5] and Hardy [6] investigated the logging data on horizontal wells on sandstone and carbonate reservoirs and indicated that the porosity has the characteristics of fGn.…”
Section: Introductionmentioning
confidence: 99%